2014
DOI: 10.4103/1673-5374.137595
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 72 confers protection in retinal ganglion cells and lateral geniculate nucleus neurons via blockade of the SAPK/JNK pathway in a chronic ocular-hypertensive rat model

Abstract: Optic nerve transection increased the expression of heat shock protein 72 (HSP72) in the lateral geniculate body, indicating that this protein is involved in the prevention of neuronal injury. Zinc sulfate and quercetin induced and inhibited the expression of HSP72, respectively. Intraperitoneal injections of zinc sulfate, SP600125 (c-Jun N-terminal kinase inhibitor), or quercetin were performed on retinal ganglion cells in a Wistar rat model of chronic ocular hypertension. Our results showed that compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The involvement of HSP70 in RGC protection was further demonstrated in animals injected with quercetin, which diminished the HSP70 expression and significantly decreased the number of surviving RGCs in the zinc-treated group (Park et al, 2001b). Zinc sulfate-induced upregulation of HSP72 was associated with blockage of the stress-activated protein kinase SAPK/JNK apoptotic pathway, and consequently with enhanced RGC and lateral geniculate nucleus neuron survival in rat glaucoma model (Li et al, 2014). …”
Section: Hsp70 and Rgc Survivalmentioning
confidence: 99%
“…The involvement of HSP70 in RGC protection was further demonstrated in animals injected with quercetin, which diminished the HSP70 expression and significantly decreased the number of surviving RGCs in the zinc-treated group (Park et al, 2001b). Zinc sulfate-induced upregulation of HSP72 was associated with blockage of the stress-activated protein kinase SAPK/JNK apoptotic pathway, and consequently with enhanced RGC and lateral geniculate nucleus neuron survival in rat glaucoma model (Li et al, 2014). …”
Section: Hsp70 and Rgc Survivalmentioning
confidence: 99%
“…The molecular weight of inducible HSP72 is 72 kDa, so it is also known as HSP72, with low expression level in non-stress state, but the expression level would markedly increase in stress state to protect during injury or repair ( 4 , 12 , 13 ). It has been shown ( 14 ) that HSP72 could protect neural pathways by interdicting the activity of apoptosis pathway SAPK/JNK in RGCs and lateral geniculate body nerve cells ( 5 ). HSP72 is considered as an apoptosis inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou and colleagues recently report quercetin alleviates the excitability of RGCs through increased miniature GABAergic neurotransmission and decreasing miniature glutamatergic neurotransmission [ 94 ]. On the other hand, some studies have demonstrated that quercetin has an inhibitory effect of heat shock protein 72 (HSP 72) in RGCs [ 95 , 96 , 97 ]. Quercetin has neuroprotective effects of retinal layers [ 98 ] and cytoprotective effects of photoreceptor, RPE and RGCs through inhibiting activity of AP-1 pathway [ 99 ] in light-induced retinal degeneration rodent models.…”
Section: Neuroprotective Effects Of Nutraceuticals In Animal Studimentioning
confidence: 99%